The School Literation Movement Strategy in Improving the Student Reading interest at Sma Negeri 4 Padang - Wenti Susanti (Postgraduate School, Universitas Negeri Padang, 2019)
The School Literacy Movement launched by the Ministry of Education and Culture in 2015 aims to foster students interest in reading because Indonesian students reading interest is still low. The objectives of this research are (1) to describe the implementation of the school literacy movement in increasing reading interest in social studies students at SMA N 4 Padang. (2) to describe the problems in the implementation of the school literacy movement in increasing the student reading interest in social studies students at SMA N 4 Padang. (3) to analyze the strategy of the school literacy movement in increasing students reading interest atSMA N 4 Padang. The approach used in this research was a qualitative approach. The selection of informants was done by using a purposive sampling. The data were obtained through observation, interviews, and documentation. The test of the validity of the data was by means of data triangulation. The data analysis technique used the analysis of the Miles and Huberman models. The results of the research indicated that the implementation of the school literacy movement in this school was held on Monday-Thursday at 13.05-13.20. There were already supporting facilities such as corners and literacy parks. Reading books came from the students. The problems faced were in the form of availability of reading material sources and available time. While the strategies carried out were (1) giving rewards in the form of literacy corner competitions and visitors to the traditional library. (2) The existence of a literacy journal to monitor the student literacy activities every day. (3) Participating in literacy competitions (4) The teachers and schools always emphasize the importance of literacy. Keywords: School Literacy Movement, Student Reading Interest